Blended Learning: Innovation in College Classrooms for Deeper Student Engagement - Sandjaja, Meilani (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Technological advancements demand adaptation in education. Blended learning, which combines face-to-face and online learning methods, can enhance student engagement among university students. Student engagement is an essential aspect that must be considered in the teaching and learning process, as it affects both the process and outcomes of students' learning. The aim of this study is to analyze the impact of implementing the blended learning method on increasing student engagement in higher education. The hypothesis of this study is that the blended learning method can enhance student engagement. This research employed a quantitative approach with a cross-sectional design. Data were collected through an online survey using a questionnaire distributed to 179 active students from various study programs who had previously participated in blended learning and were aged between 18 and 22 years. The results showed that blended learning had a positive and significant effect on student engagement (t = 8.121, p < .001). Perceptions of blended learning contributed 26.7% to student engagement (Adjusted R² = 0.267). The findings of this study indicate that the implementation of the blended learning method can enhance student engagement at the higher education level. The implication of this research is that the implementation of blended learning can create a more flexible and easily accessible learning experience, allowing students to adapt their learning process to their individual needs and pace. This has a positive impact on their learning engagement. Kemajuan teknologi menuntut adaptasi dalam pendidikan. Blended learning yang menggabungkan metode belajar tatap muka dan daring dapat meningkatkan student engagement mahasiswa. Student engagement merupakan aspek penting yang perlu diperhatikan dalam proses belajar dan mengajar karena akan berpengaruh pada proses dan hasil belajar mahasiswa. Tujuan dari penelitian ini adalah menganalisis pengaruh penerapan metode blended learning terhadap peningkatan student engagement pada mahasiswa di perguruan tinggi. Hipotesis penelitian ini adalah metode blended learning mampu meningkatkan student engagement mahasiswa. Penelitian ini menggunakan pendekatan kuantitatif dengan desain cross-sectional. Data dikumpulkan melalui survei daring menggunakan kuesioner yang dibagikan kepada 179 mahasiswa aktif dari berbagai program studi yang pernah mengikuti pembelajaran blended learning dan berusia antara 18 hingga 22 tahun. Hasil penelitian menunjukkan bahwa blended learning berpengaruh positif dan signifikan terhadap student engagement (t = 8.121, p < .001). Persepsi terhadap blended learning memberikan kontribusi sebesar 26.7% terhadap student engagement (Adjusted R² = 0.267). Hasil yang diperoleh dari penelitian ini adalah penerapan metode blended learning dapat meningkatkan student engagement mahasiswa di tingkat perguruan tinggi. Implikasi penelitian ini adalah penerapan blended learning dapat menciptakan pengalaman belajar yang lebih fleksibel dan mudah diakses, memungkinkan mahasiswa untuk menyesuaikan proses belajar dengan kebutuhan dan kecepatan masing-masing. Hal ini memberikan dampak positif bagi ketelibatan belajar mereka.